Arquivos e Informação: os caminhos da gestão de documentos na Universidade Federal da Paraíba - Amorim, Ana Andrea Vieira Castro de (2011)
The management of archival documents has presented itself as a major challenge for the Public Institutions. In the Federal Institutions of higher education, this process has not been different. The creation of a national politics of archives that determines to be duty of the Public Authorities the management of documents comes contributing gradually for the change of that setting. This research sought to analyze the deployment process of the bases of the management of documents in the Paraiba Federal University, from the actions developed by the Permanent commission of Document Evaluation. It argued definitions, objects and approaches of the Archival science and the Science of the Information. It presented of general form document archive concepts, archive and archival information. It was characterized as a descriptive and exploratory research, with quantitative and qualitative approaches; having the case study as strategy and did use as instruments of collects of data: interviews and questionnaires. It was found through this research, the absence of actions directed toward an effective management of the documents in the current archives, as also, the emergent need of implementation of policies institutional archival.